Comparative metagenomics of microbial mats from hypersaline lakes at Rottnest Island (WA, Australia), advancing our understanding of the effect of mat community and functional genes on microbialite accretion. (16th September 2019) - Mendes Monteiro, Juliana; Vogwill, Ryan; Bischoff, Karl; Gleeson, Deirdre B.
Abstract: Microbial mats are organosedimentary structures organized as multilayered carpets of microbial communities. Within the microbial mat microenvironment, the occurrence of different metabolic processes can lead to local chemistry alterations, inducing carbonate precipitation. Carbonate accretion in lithifying microbial mats typically induces microbialite formation, a poorly understood process, but studies have suggested that taxonomic composition of lithifying mats and their predominant metabolic pathways contribute. In contrast to lithifying mats, non‐lithifying mats, which do not form microbialites, can sporadically trap carbonate sand grains that are actively bound to the microbial mat through the production of extracellular polymeric substances. Both mat types occur in hypersaline lakes at Rottnest Island (Western Australia) and are currently under threat due to pollution and thus are being managed by the relevant government agency. Characterizing the microbial communities and functional genes of both mat types may help to develop strategies to better manage their ecosystem and elucidate microbialite formation processes. Metagenomics was used to compare the taxonomic and functional diversity of both mat types to determine whether differences in their taxonomy and functional capacity may influence their ability to form microbialites. Results revealed that both mat types harbor taxa (e.g., Firmicutes and Archaea), and functional genes (e.g., associated with photosynthesis, carbon, and sulfur cycles) that are known to play important roles in microbialite formation. This suggests that although non‐lithifying mats are not accreting carbonate, they have the potential to form microbialites. Further investigation is needed to determine whether environmental factors could be inhibiting carbonate precipitation within these mats.